ZSM-5 molecular sieve and preparation and application thereof

By adopting a specific ZSM-5 molecular sieve preparation method, the problem of short catalyst life in the prior art is solved, the catalyst life is extended and the catalytic performance is improved, and it is particularly suitable for the alkylation reaction of benzene and high concentration ethylene.

CN119612541AActive Publication Date: 2025-03-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202311174213.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-14
Estimated Expiration
2043-09-12

AI Technical Summary

Technical Problem

In the prior art, the life of the catalyst used to ethylbenzene is shorter, resulting in frequent regeneration of catalysts, which increases costs and affects the normal production of the device.

Method used

A ZSM-5 molecular sieve preparation method is adopted to prepare a ZSM-5 molecular sieve catalyst with excellent catalytic properties through specific mixture treatment and condition control. The method includes mixing a silicon source, an aluminum source, water and a template agent, undergoing sealing treatment, followed by adding organic matter and re-sealing treatment, and finally obtaining a ZSM-5 molecular sieve by crystallization, liquid-solid separation, washing and drying.

Benefits of technology

It significantly extends the service life of the catalyst, improves the ethylene conversion rate, inhibits side reactions, and enhances the ethyl selectivity in the alkylation products. It is especially suitable for the alkylation reaction of benzene and high concentrations of ethylene.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612541A_ABST
    Figure CN119612541A_ABST
Patent Text Reader

Abstract

The invention discloses a ZSM-5 molecular sieve as well as preparation and application thereof. The preparation method of the ZSM-5 molecular sieve comprises the following steps: (a) mixing a silicon source I, an aluminum source I, water and a template agent I, and carrying out first sealing treatment to obtain a mixture A; (b) mixing the mixture A with an organic matter I, and carrying out secondary sealing treatment to obtain a mixture B; (c) mixing the mixture B, a silicon source II, an aluminum source II, water, a template agent II and an organic matter II to obtain a mixture C; and (d) crystallizing the mixture C, and carrying out liquid-solid separation, washing and drying to obtain the molecular sieve, the conditions of the first airtight treatment are as follows: the temperature is 10-40 DEG C, and the time is 5-15 hours; the conditions of the second airtight treatment are as follows: the temperature is 80-130 DEG C, and the time is 1-5 hours. A catalyst prepared from the ZSM-5 molecular sieve is used for a reaction for preparing ethylbenzene through alkylation of benzene and ethylene, and the service life of the catalyst is obviously prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalytic chemistry and chemical engineering, and in particular relates to a ZSM-5 molecular sieve and its preparation and application. Background Art

[0002] Ethylbenzene is an important organic chemical raw material and plays a vital role in the development of the national economy. Ethylbenzene is mainly used in the downstream production of styrene, and then in the production of polymer materials such as ABS and PS, which are widely used in the fields of automobiles, electronics, aviation, urban construction or daily necessities.

[0003] More than 90% of ethylbenzene is produced by alkylation reaction of benzene and ethylene under the action of acidic molecular sieves. According to different reaction processes, it can be divided into liquid phase method and gas phase method. Among them, the gas phase method is suitable for different ethylene raw materials, which can be pure ethylene, dilute ethylene or ethanol. The reaction temperature of the gas phase method is higher than 320°C. During the reaction process, a series of side reactions are likely to occur, producing heavy components and tar. After a long period of reaction, carbon deposits are formed to block the pores of the molecular sieve, resulting in a decrease in the activity of the catalyst, and the catalyst needs to be regenerated. Developing catalysts with long-term stability characteristics, extending the service life of the catalyst, and reducing the number of regenerations can effectively save costs and affect the normal production of the device as little as possible.

[0004] CN102875316A discloses a method for preparing ethylbenzene by alkylation of dry gas and benzene, wherein dry gas and benzene are used as reaction raw materials, and the reaction raw materials are contacted with a catalyst to undergo a gas-phase alkylation reaction to produce ethylbenzene; the catalyst used contains the following components by weight percentage: a) 40-90% of a ZSM-5 molecular sieve having a grain diameter of 5-500 nanometers and a silicon-aluminum molar ratio SiO2 / Al2O3 of 30-400; b) 9-59% of a binder alumina or silicon dioxide; c) 0.1-10% of an alkaline earth metal oxide and 0.1-10% of a rare earth metal oxide; the technical solution of treating the catalyst with high-temperature steam solves the problems of poor catalyst stability and short regeneration cycle, but the method is applicable to dry gas, in which the ethylene mass concentration is generally 10-20wt.%, and it is not further specified whether it is applicable to raw gas with a higher ethylene concentration.

[0005] CN108080019A discloses a method for preparing a highly selective benzene alkylation strip catalyst, which comprises selecting a high silicon-aluminum ratio MFI zeolite molecular sieve as the matrix of the catalyst; extruding the hydrolyzate of acidified silicone grease and the high silicon-aluminum ratio MFI zeolite molecular sieve into strips, treating the formed catalyst with the separated mother liquor obtained by hydrothermal crystallization of the high silicon-aluminum ratio MFI zeolite molecular sieve, and adding boride to the separated mother liquor; and converting the high silicon-aluminum ratio MFI zeolite molecular sieve extruded strips treated with the mother liquor into a hydrogen-type alkylation catalyst by an ion exchange method. The method uses the mother liquor generated during the hydrothermal synthesis of the high silicon-aluminum ratio MFI zeolite molecular sieve to treat the formed strip catalyst, which not only recovers the useful components in the mother liquor, dredges the pores of the catalyst, but also reduces the environmental pollution in the entire production chain of the alkylation catalyst. When the mother liquor is used to treat the formed catalyst, the mechanical strength of the catalyst particles is improved by adding an appropriate amount of boride to the mother liquor, which is beneficial to prolonging the service life of the catalyst. However, this method does not make a detailed comparison of the specific lifespan of the catalyst, and the applicable raw material is ethanol, without further explanation as to whether it is applicable to dilute ethylene or pure ethylene raw materials. Summary of the invention

[0006] In view of the problem that the catalyst life of ethylbenzene produced by alkylation of benzene and ethylene is short in the prior art, the present invention provides a ZSM-5 molecular sieve and its preparation and application. The catalyst prepared by the ZSM-5 molecular sieve of the present invention is particularly suitable for the reaction of alkylation of benzene and high-concentration ethylene to produce ethylbenzene, and the catalyst life is significantly extended.

[0007] The first aspect of the present invention provides a method for preparing a ZSM-5 molecular sieve, comprising:

[0008] (a) mixing a silicon source I, an aluminum source I, water and a template agent I, and subjecting the mixture to a first sealing treatment to obtain a mixture A;

[0009] (b) mixing the mixture A and the organic matter I, and subjecting the mixture to a second sealing treatment to obtain a mixture B;

[0010] (c) mixing mixture B, silicon source II, aluminum source II, water, template II and organic matter II to obtain mixture C;

[0011] (d) crystallizing the mixture C, performing liquid-solid separation, washing, and drying to obtain the molecular sieve;

[0012] The first sealed treatment conditions are: temperature 10-40°C, time 5-15 hours; the second sealed treatment conditions are: temperature 80-130°C, time 1-5 hours.

[0013] In the above technical solution, preferably, step (a) has one or more of the following characteristics:

[0014] In the above technical solution, preferably, in step (a), the silicon source I is one or more of tetraethyl silicate, tetrapropyl silicate, and tetrabutyl silicate;

[0015] In the above technical solution, preferably, in step (a), the aluminum source I is one or more of aluminum sulfate, aluminum isopropoxide, sodium aluminate, and pseudo-boehmite;

[0016] In the above technical scheme, preferably, in step (a), the template agent I is one or more of tetrapropylammonium hydroxide, ethylamine, ethylenediamine, n-butylamine, butanediamine, hexamethyleneimine, piperidine, piperazine, and homopiperazine;

[0017] In the above technical scheme, preferably, preferably, in step (a), the molar ratios of silicon source I, aluminum source I, water and template I are respectively silicon source I: aluminum source I: water: template I = 1: (0.0025-0.025): (5-20): (0.1-1.0), wherein silicon source I and aluminum source I are calculated as SiO2 and Al2O3, respectively.

[0018] In the above technical solution, preferably, the first closed treatment in step (a) and the second closed treatment in step (b) are both carried out under stirring conditions.

[0019] In the above technical scheme, preferably, the organic substance I in step (b) is an aminopropyl-containing silane, preferably one or more of diethylenetriaminopropylmethyldimethoxysilane, N-aminoethyl-3-aminopropylmethyldiethoxysilane or N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane.

[0020] In the above technical solution, preferably, the molar ratio of the organic matter I to the mixture A in terms of SiO2 is organic matter I:SiO2=(0.02-0.3):1.

[0021] In the above technical solution, preferably, step (c) has one or more of the following characteristics:

[0022] In the above technical solution, preferably, in step (c), the silicon source II is one or more of silica sol, white carbon black, silicon powder, tetramethyl silicate, tetraethyl silicate, tetrapropyl silicate, and tetrabutyl silicate;

[0023] In the above technical solution, preferably, in step (c), the aluminum source II is one or more of aluminum nitrate, aluminum chloride, aluminum sulfate, aluminum isopropoxide, sodium aluminate, and pseudo-boehmite;

[0024] In the above technical scheme, preferably, in step (c), the template agent II is one or more of tetrapropylammonium bromide, tetrapropylammonium hydroxide, ethylamine, ethylenediamine, n-propylamine, propylenediamine, n-butylamine, butylenediamine, n-hexylamine, hexamethylenediamine, ammonia water, hexamethyleneimine, piperidine, piperazine, and homopiperazine;

[0025] In the above technical scheme, preferably, the organic substance II in step (c) is a disilazane containing a phenyl group, preferably one or more of 1,3-diphenyltetraethyldisilazane, 1,3-dichloro-1,1,3,3-tetraphenyldisilazane or 1,3-dimethyl-1,1,3,3-tetraphenyldisilazane.

[0026] In the above technical scheme, preferably, in step (c), the molar ratios of silicon source II, aluminum source II, water, template II and organic matter II are respectively silicon source II: aluminum source II: water: template II: organic matter II = 1: (0.0025-0.025): (8-20): (0.1-0.3): (0.005-0.20), and the ratio of the mass of the mixture B to the total mass of the five substances of silicon source II, aluminum source II, water, template II and organic matter II is (0.04-0.22): 1, wherein the silicon source II and the aluminum source II are calculated as SiO2 and Al2O3, respectively.

[0027] In the above technical solution, preferably, the crystallization conditions in step (d) are crystallization at 130-180° C. for 12-60 hours under closed conditions.

[0028] The second aspect of the present invention provides a ZSM-5 molecular sieve prepared by the preparation method of the first aspect.

[0029] In the above technical solution, the static water initial contact angle of the molecular sieve is 110-160°, and the static benzene adsorption capacity is 180-230 mg / g.

[0030] In the above technical solution, preferably, the b-axis thickness of the ZSM-5 molecular sieve is 10-95 nm, preferably 30-90 nm, and the exposure of the crystal plane perpendicular to the b-axis is 67%-78%, preferably 65%-76%.

[0031] In the above technical solution, preferably, the SiO2 / Al2O3 molar ratio of the ZSM-5 molecular sieve is 40-400.

[0032] The third aspect of the present invention provides a catalyst for preparing ethylbenzene by alkylation of benzene, wherein the catalyst comprises a ZSM-5 molecular sieve, and the synthesized state of the ZSM-5 molecular sieve is the molecular sieve prepared by the method of the first aspect.

[0033] In the above technical solution, in the catalyst, the ZSM-5 molecular sieve exists in a calcined state.

[0034] In the above technical solution, the catalyst, in addition to the molecular sieve, optionally includes aluminum oxide, silicon oxide or a mixture thereof.

[0035] In the above technical solution, preferably, the catalyst may also include alumina, and based on the mass of the catalyst, the content of the molecular sieve is more than 80%, preferably 80%-90%, and the content of alumina is less than 20%, preferably 10%-20%.

[0036] In the above technical solution, preferably, the micropore volume of the catalyst is 0.12-0.16cm 3 ·g -1 , the mesopore volume is 0.42-0.80cm 3 ·g -1 , mechanical strength is 70-110N / cm, bulk density is 0.51-0.65g·cm -3 .

[0037] A fourth aspect of the present invention provides a method for preparing a catalyst for preparing ethylbenzene by alkylation of benzene, comprising:

[0038] (e) The ZSM-5 molecular sieve prepared in the first aspect, alumina and a polymer mixture are mixed and molded, and then dried, calcined, ammonium exchanged, steam treated, and acid washed to obtain the catalyst.

[0039] In the above technical solution, preferably, step (e) has one or more of the following characteristics:

[0040] In the above technical solution, preferably, the alumina in step (e) is alumina monohydrate;

[0041] In the above technical solution, preferably, in step (e), the polymer mixture is a mixture of starch and at least one substance selected from hexadecyltrimethylammonium bromide, P123 or F127, wherein the mass ratio of starch to the polymer mixture is 60%-70%;

[0042] In the above technical solution, preferably, in step (e), the mass ratio of molecular sieve, alumina and polymer mixture is: molecular sieve: alumina: polymer mixture = 1: (0.1-0.3): (0.05-0.1);

[0043] In the above technical solution, preferably, a molding aid may be added in step (e), such as at least one of dilute nitric acid, sesbania powder, etc.;

[0044] In the above technical solution, preferably, the dilute nitric acid in step (e) is preferably an aqueous solution of nitric acid, with a mass concentration of 1.5%-7%;

[0045] In the above technical solution, preferably, in step (e), the mass ratio of molecular sieve, dilute nitric acid and sesbania powder is: molecular sieve: dilute nitric acid: sesbania powder = 1: (0.8-1.0): (0.03-0.05);

[0046] In the above technical solution, preferably, the molding in step (e) is preferably extrusion molding, followed by drying, roasting, ammonium exchange, steam, and acid washing;

[0047] In the above technical scheme, preferably, in step (e), the drying condition is 120-150° C. for 5-15 hours; the roasting condition is 400-600° C. for 4-10 hours; the ammonium exchange condition is using an ammonium salt solution with a mass concentration of 2%-8% at 20-90° C. for 2-5 hours, and the exchange is continuous for 4 times, and the ammonium salt is one of ammonium sulfate, ammonium chloride, ammonium acetate or ammonium nitrate; the water vapor treatment condition is 420-520° C. for 4-10 hours in a saturated water vapor atmosphere; the pickling condition is using an acid solution with a mass concentration of 0.5%-3.0% at 20-90° C. for 2-5 hours, and the acid is at least one of hydrochloric acid, sulfuric acid, nitric acid or oxalic acid.

[0048] The fifth aspect of the present invention provides a catalyst for producing ethylbenzene by alkylation of benzene prepared by the method of the fourth aspect.

[0049] In the above technical solution, preferably, the catalyst has a molecular sieve content of more than 80%, preferably 80%-90%, and an alumina content of less than 20%, preferably 10%-20%, based on the mass of the catalyst.

[0050] In the above technical solution, preferably, the micropore volume of the catalyst is 0.12-0.16cm 3 ·g -1 , the mesopore volume is 0.42-0.80cm 3 ·g -1 , mechanical strength is 70-110N / cm, bulk density is 0.51-0.65g·cm -3 .

[0051] A sixth aspect of the present invention provides a method for preparing ethylbenzene by alkylating benzene, wherein the reaction raw materials benzene and ethylene are contacted with the above-mentioned ZSM-5 molecular sieve catalyst to generate ethylbenzene.

[0052] In the above technical solution, preferably, the mass concentration of ethylene in the ethylene raw material is 8%-100%.

[0053] In the above technical solution, preferably, the reaction temperature is 300-380°C, the reaction pressure is 0.4-2.5MPa, and the ethylene mass space velocity is 0.1-3.0h -1 , the molar ratio of benzene to ethylene is 4.0-6.0.

[0054] Compared with the prior art, the present invention has the following beneficial effects:

[0055] 1. The inventors of the present invention have found through research that when the static water initial contact angle of the ZSM-5 molecular sieve is in the range of 110-160°, the outer surface is hydrophobic, and the static benzene adsorption amount is 180-230 mg / g, during the molding process, the condensation of the binder with the silanol groups on the surface of the molecular sieve can be effectively inhibited, the pore blocking effect of the binder can be reduced, and the pore volume of the catalyst can be increased, which is beneficial to improving the comprehensive performance of the catalyst, especially prolonging the life of the catalyst in the alkylation reaction of benzene and ethylene to produce ethylbenzene.

[0056] 2. The inventor of the present invention has found through research that the b-axis thickness of the ZSM-5 molecular sieve and the exposure of the crystal plane perpendicular to the b-axis are crucial to the performance of the benzene alkylation catalyst. Since the crystal growth process of the ZSM-5 molecular sieve follows the Ostwald-ripening and Wulff Construction rules, the ZSM-5 molecular sieve prepared by the conventional method is mostly coffin morphology, and the b-axis thickness and the exposure of the crystal plane perpendicular to the b-axis are difficult to control. The inventor has found through further research that in the process of preparing the molecular sieve, silane containing aminopropyl and silane containing phenyl are introduced at different times, and the closed treatment conditions are controlled twice, so that the b-axis thickness of the molecular sieve can be effectively controlled to be 10-95nm, preferably 30-90nm, and the exposure of the crystal plane perpendicular to the b-axis is 67%-78%, preferably 65%-76%. The ZSM-5 molecular sieve of the present invention is used in the reaction of benzene alkylation to ethylbenzene, which is obviously beneficial to improve the ethylene conversion rate, inhibit side reactions, improve the ethyl selectivity in the alkylation product, and prolong the life of the catalyst, and is particularly suitable for the reaction of benzene alkylation to ethylbenzene. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 The XRD spectrum of the molecular sieve prepared in Example 1 of the present invention;

[0058] Figure 2 This is a photograph of the static water initial contact angle of the molecular sieve prepared in Example 1 of the present invention;

[0059] Figure 3 XRD spectrum of the molecular sieve prepared in Comparative Example 1 of the present invention;

[0060] Figure 4 This is a photograph of the static water initial contact angle of the molecular sieve prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0061] The present invention is described in detail below in conjunction with specific implementation modes, but it should be understood that the protection scope of the present invention is not limited by the specific implementation modes.

[0062] The b-axis thickness of the molecular sieve and the exposure of the crystal plane perpendicular to the b-axis direction in the present invention are obtained by analyzing SEM photos, and the SEM photos are obtained using a Hitachi S-4800 cold field emission high-resolution scanning electron microscope produced by Hitachi. Among them, the exposure of the crystal plane perpendicular to the b-axis direction is the ratio of the area of ​​the ZSM-5 molecular sieve 010 crystal plane to the total area of ​​all crystal planes.

[0063] In the present invention, the micropore volume and the mesopore volume are obtained by nitrogen adsorption-desorption test. The nitrogen adsorption-desorption isotherm of the catalyst is tested at liquid nitrogen temperature using a BEL-MAX specific surface area and pore size analyzer produced by BELSORP Co., Ltd. of Japan. The total pore volume is calculated using the BET equation, and the micropore volume is calculated using the t-plot method. The difference between the total pore volume and the micropore volume is the mesopore volume.

[0064] In the present invention, the mechanical strength is obtained by using an intelligent particle strength tester. The DLIII type intelligent particle strength tester of Dalian Penghui Technology Development Co., Ltd. is used to test the mechanical strength of the catalyst. The length of the measured catalyst is 5 mm, and it is placed horizontally on the tester to test the maximum pressure that the catalyst can withstand when it is broken. After testing the crushing strength of 20 catalysts, the average value is taken.

[0065] In the present invention, the XRD spectrum of the catalyst was obtained by using the Ultima IV X-ray powder diffractometer produced by Rigaku Corporation of Japan. The voltage was selected as 35 kV, the current was selected as 30 mA, and the scanning speed was 1°·min -1 .

[0066] In the present invention, the bulk density of the catalyst is calculated by dividing the actual weight of the added catalyst (unit: g) by the actual volume using a 1000 mL graduated cylinder as the container, and the unit is g·cm -3 .

[0067] In the present invention, the SiO2 / Al2O3 molar ratio is obtained by ICP testing, and the ICP test is performed using a Kontron Model S-35 ICP-AES analyzer to obtain silicon-aluminum ratio data.

[0068] In the present invention, a Chengde Dingsheng JY-82C video contact angle tester is used to test and obtain the static water initial contact angle of the molecular sieve, an appropriate amount of ground powder sample is placed on a tablet press to be pressed into a sheet, and then placed on a contact angle test platform, water drops are dripped on the automatic titration system of the equipment, test photos are taken, and then the angle of the contact angle is measured by the angle measurement method.

[0069] In the present invention, the static benzene adsorption capacity is tested by using a BSD-VVS multi-station gravimetric gas vapor adsorption instrument produced by Best Instrument Technology Co., Ltd. The sample is activated at 250°C for 6 hours under vacuum conditions before the test. The cumulative adsorption capacity of benzene by the sample when the relative pressure P / P0 is 0.90 is taken as the final static benzene adsorption capacity.

[0070] [Example 1]

[0071] This example is used to synthesize a ZSM-5 molecular sieve and a ZSM-5 molecular sieve catalyst. The specific preparation process is as follows:

[0072] 416.6 g of tetraethyl silicate, 20 g of aluminum sulfate 18hydrate, 576 g of water and 122 g of tetrapropylammonium hydroxide are mixed evenly, and then stirred at 30°C for 10 hours under closed conditions to obtain mixture A1; then 74.8 g of diethylenetriaminopropylmethyldimethoxysilane is added to the above mixture A1 and mixed evenly, and stirred at 110°C for 2 hours under closed conditions to obtain mixture B1, wherein tetraethyl silicate is calculated as SiO2: aluminum sulfate 18hydrate is calculated as Al2O3: water: tetrapropylammonium hydroxide: diethylenetriaminopropylmethyldimethoxysilane = 1:0.015:16:0.3:0.15 (molar ratio). Mix 69.3 g of mixture B1, 120 g of silicon powder, 20 g of aluminum sulfate 18 hydrate, 468 g of water, 44.1 g of diamine and 41 g of 1,3-diphenyltetraethyldisilazane to obtain mixture C1, wherein silicon powder is calculated as SiO2: aluminum sulfate 18 hydrate is calculated as Al2O3: water: n-butylamine: 1,3-diphenyltetraethyldisilazane = 1: 0.015: 13: 0.25: 0.06 (molar ratio). C1 is crystallized at 165° C. for 36 h in a sealed container, then centrifuged to obtain a solid, washed with deionized water for multiple times until the pH of the washing liquid reaches 7.0, and then dried at 150° C. for 8 hours to obtain molecular sieve D1.

[0073] 1000 g of molecular sieve D1, 200 g of alumina monohydrate, 950 g of 3.5% nitric acid aqueous solution, 45 g of sesbania powder and 80 g of a polymer mixture (including 52 g of starch and 28 g of hexadecyltrimethylammonium bromide) are mixed and extruded into a cylindrical shape, and then treated at 135° C. for 10 hours; 520° C. for 4 hours; treated at 70° C. for 2 hours with 5% ammonium chloride solution, and exchanged 4 times continuously; treated at 490° C. in a saturated water vapor atmosphere for 7 hours; and treated at 70° C. for 4 hours with 1.5% oxalic acid solution to obtain catalyst E1.

[0074] The XRD spectrum of molecular sieve D1 is as follows Figure 1As shown, it has a typical ZSM-5 molecular sieve diffraction peak. The static water initial contact angle photo of molecular sieve D1 is shown in Figure 2 As shown, the value is 133.5°, and the static benzene adsorption is 210 mg / g. The b-axis thickness of the molecular sieve is 75 nm, and the exposure of the crystal plane perpendicular to the b-axis is 72%. The SiO2 / Al2O3 molar ratio of the molecular sieve D1 is 66.

[0075] Through testing, the micropore volume of catalyst E1 is 0.14 cm 3 ·g -1 , the mesopore volume is 0.63 cm 3 ·g -1 , mechanical strength is 95N / cm, bulk density is 0.54g·cm -3 .

[0076] [Example 2]

[0077] This example is used to synthesize a ZSM-5 molecular sieve and a ZSM-5 molecular sieve catalyst. The specific preparation process is as follows:

[0078] 264.4 g of tetrapropyl silicate, 16.67 g of aluminum sulfate 18hydrate, 360 g of water and 45.1 g of ethylamine were mixed evenly, and then stirred at 40°C for 5 hours under closed conditions to obtain mixture A2; then 70.3 g of N-aminoethyl-3-aminopropylmethyldiethoxysilane was added to the above mixture A2 and mixed evenly, and stirred at 130°C for 1 hour under closed conditions to obtain mixture B2, wherein tetrapropyl silicate is calculated as SiO2: aluminum sulfate 18hydrate is calculated as Al2O3: water: ethylamine: N-aminoethyl-3-aminopropylmethyldiethoxysilane = 1:0.025:20:1.0:0.3 (molar ratio). 119.4 g of mixture B2, 60 g of white carbon, 16.67 g of aluminum sulfate 18-hydrate, 360 g of water, 61 g of tetrapropylammonium hydroxide and 67.5 g of 1,3-dichloro-1,1,3,3-tetraphenyldisilazane were mixed to obtain mixture C2, wherein white carbon was calculated as SiO2: aluminum sulfate 18-hydrate was calculated as Al2O3: water: tetrapropylammonium hydroxide: 1,3-dichloro-1,1,3,3-tetraphenyldisilazane = 1: 0.025: 20: 0.3: 0.15 (molar ratio). C2 was crystallized at 180° C. for 12 h in a sealed container, then centrifuged to obtain a solid, washed the solid with deionized water for multiple times until the pH of the washing liquid reached 7.0, and then dried the washed solid at 150° C. for 8 hours to obtain molecular sieve D2.

[0079] 1000 g of molecular sieve D2, 300 g of alumina monohydrate, 1000 g of 7% nitric acid aqueous solution, 50 g of sesbania powder and 100 g of a polymer mixture (including 70 g of starch and 30 g of P123) were mixed and extruded into a four-leaf clover shape, and then treated at 150°C for 5 hours; 600°C for 4 hours; treated with 8% ammonium nitrate solution at 90°C for 3 hours, and exchanged 4 times continuously; treated at 520°C in a saturated water vapor atmosphere for 10 hours; treated with 3.0% nitric acid solution at 90°C for 2 hours to obtain catalyst E2.

[0080] The XRD spectrum of molecular sieve D2 has typical ZSM-5 molecular sieve diffraction peaks. The static water initial contact angle value of molecular sieve D2 is 155.6°, and the static benzene adsorption capacity is 185 mg / g. The b-axis thickness of the molecular sieve is 35nm, and the exposure of the crystal plane perpendicular to the b-axis direction is 75%. The SiO2 / Al2O3 molar ratio of molecular sieve D2 is 42.

[0081] Through testing, the micropore volume of catalyst E2 is 0.13 cm 3 ·g -1 , the mesopore volume is 0.78 cm 3 ·g -1 , mechanical strength is 105N / cm, bulk density is 0.62g·cm -3 .

[0082] [Example 3]

[0083] This example is used to synthesize a ZSM-5 molecular sieve and a ZSM-5 molecular sieve catalyst. The specific preparation process is as follows:

[0084] 208.3 g of tetraethyl silicate, 1.02 g of aluminum isopropoxide, 90 g of water and 8.5 g of piperidine were mixed evenly, and then stirred at 10° C. for 15 hours under closed conditions to obtain a mixture A3; then 7 g of N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane was added to the above mixture A3 and mixed evenly, and stirred at 80° C. for 5 hours under closed conditions to obtain a mixture B3, wherein tetraethyl silicate is calculated as SiO2: aluminum isopropoxide is calculated as Al2O3: water: piperidine: N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane = 1:0.0025:5:0.1:0.02 (molar ratio). Mix 14.7 g of mixture B3, 208.3 g of tetraethyl silicate, 1.67 g of aluminum sulfate 18 hydrate, 144 g of water, 11.6 g of hexamethylenediamine and 2.1 g of 1,3-dimethyl-1,1,3,3-tetraphenyldisilazane to obtain mixture C3, wherein tetraethyl silicate is calculated as SiO2: aluminum sulfate 18 hydrate is calculated as Al2O3: water: hexamethylenediamine: 1,3-dimethyl-1,1,3,3-tetraphenyldisilazane = 1: 0.0025: 8: 0.1: 0.005 (molar ratio). C3 is crystallized at 130° C. for 60 h in a sealed container, then centrifuged to obtain a solid, washed the solid with deionized water for multiple times until the pH of the washing liquid reaches 7.0, and then dried at 150° C. for 8 hours to obtain molecular sieve D3.

[0085] 1000 g of molecular sieve D3, 100 g of alumina monohydrate, 800 g of 1.5% nitric acid aqueous solution, 30 g of sesbania powder and 50 g of a polymer mixture (including 30 g of starch and 20 g of hexadecyltrimethylammonium bromide) are mixed and extruded into a cylindrical shape, and then treated at 120°C for 15 hours; treated at 400°C for 10 hours; treated with 2% ammonium chloride solution at 20°C for 5 hours, and exchanged 4 times continuously; treated at 420°C in a saturated water vapor atmosphere for 10 hours; treated with 0.5% sulfuric acid solution at 20°C for 5 hours to obtain catalyst E3.

[0086] The XRD spectrum of molecular sieve D3 has typical ZSM-5 molecular sieve diffraction peaks. The static water initial contact angle value of molecular sieve D3 is 110.2°, and the static benzene adsorption capacity is 230mg / g. The b-axis thickness of the molecular sieve is 87nm, and the exposure of the crystal plane perpendicular to the b-axis direction is 70%. The SiO2 / Al2O3 molar ratio of molecular sieve D3 is 398.

[0087] Through testing, the micropore volume of catalyst E3 is 0.16cm 3 ·g -1 , the mesopore volume is 0.43 cm 3 ·g -1, mechanical strength is 72N / cm, bulk density is 0.52g·cm -3 .

[0088] [Comparative Example 1]

[0089] Compared with Example 1, the only difference is that diethylenetriaminepropylmethyldimethoxysilane is not added. The specific preparation process of ZSM-5 molecular sieve and ZSM-5 molecular sieve catalyst is as follows:

[0090] 416.6 g of tetraethyl silicate, 20 g of aluminum sulfate 18hydrate, 576 g of water and 122 g of tetrapropylammonium hydroxide were mixed evenly, and then stirred at 30°C for 10 hours under closed conditions to obtain a mixture dA1; then stirred at 110°C for 2 hours under closed conditions to obtain a mixture dB1, wherein tetraethyl silicate is calculated as SiO2: aluminum sulfate 18hydrate is calculated as Al2O3: water: tetrapropylammonium hydroxide = 1:0.015:16:0.3 (molar ratio). 69.3 g of mixture dB1, 120 g of silicon powder, 20 g of aluminum sulfate 18 hydrate, 468 g of water, 44.1 g of diamine and 41 g of 1,3-diphenyltetraethyldisilazane were mixed to obtain mixture dC1, wherein silicon powder was calculated as SiO2: aluminum sulfate 18 hydrate was calculated as Al2O3: water: n-butylamine: 1,3-diphenyltetraethyldisilazane = 1: 0.015: 13: 0.25: 0.06 (molar ratio). dC1 was crystallized at 165°C for 36 hours in a sealed container, then centrifuged to obtain a solid, washed the solid with deionized water for multiple times until the pH of the washing liquid reached 7.0, and then dried the washed solid at 150°C for 8 hours to obtain molecular sieve dD1.

[0091] 1000 g of molecular sieve dD1, 200 g of alumina monohydrate, 950 g of 3.5% nitric acid aqueous solution, 45 g of sesbania powder and 80 g of a polymer mixture (including 52 g of starch and 28 g of hexadecyltrimethylammonium bromide) are mixed and extruded into a cylindrical shape, and then treated at 135°C for 10 hours; 520°C for 4 hours; treated with 5% ammonium chloride solution at 70°C for 2 hours, and exchanged 4 times continuously; treated at 490°C in a saturated water vapor atmosphere for 7 hours; and treated with 1.5% oxalic acid solution at 70°C for 4 hours to obtain the catalyst dE1.

[0092] The XRD spectrum of molecular sieve dD1 is as follows Figure 3 As shown, it has a typical ZSM-5 molecular sieve diffraction peak. The static water initial contact angle photo of molecular sieve dD1 is shown in Figure 4As shown, the value is 44.2°, and the static benzene adsorption is 145 mg / g. The b-axis thickness of the molecular sieve is 148 nm, and the exposure of the crystal plane perpendicular to the b-axis is 45%. The SiO2 / Al2O3 molar ratio of the molecular sieve dD1 is 65.

[0093] Through testing, the micropore volume of catalyst dE1 is 0.11cm 3 ·g -1 , the mesopore volume is 0.61cm 3 ·g -1 , mechanical strength is 92N / cm, bulk density is 0.55g·cm -3 .

[0094] [Comparative Example 2]

[0095] Compared with Example 1, the only difference is that 1,3-diphenyltetraethyldisilazane is not added. The specific preparation process of ZSM-5 molecular sieve and ZSM-5 molecular sieve catalyst is as follows:

[0096] 416.6 g of tetraethyl silicate, 20 g of aluminum sulfate 18hydrate, 576 g of water and 122 g of tetrapropylammonium hydroxide were mixed evenly, and then stirred at 30°C for 10 hours under closed conditions to obtain a mixture dA2; then 74.8 g of diethylenetriaminopropylmethyldimethoxysilane was added to the above mixture dA2 and mixed evenly, and stirred at 110°C for 2 hours under closed conditions to obtain a mixture dB2, wherein tetraethyl silicate is calculated as SiO2: aluminum sulfate 18hydrate is calculated as Al2O3: water: tetrapropylammonium hydroxide: diethylenetriaminopropylmethyldimethoxysilane = 1:0.015:16:0.3:0.15 (molar ratio). Mix 69.3 g of mixture dB2, 120 g of silicon powder, 20 g of aluminum sulfate 18 hydrate, 468 g of water and 44.1 g of dibutylamine to obtain mixture dC2, wherein silicon powder is calculated as SiO2: aluminum sulfate 18 hydrate is calculated as Al2O3: water: n-butylamine = 1: 0.015: 13: 0.25 (molar ratio). dC2 is crystallized at 165°C for 36 hours in a sealed container, then centrifuged to obtain a solid, washed with deionized water for multiple times until the pH of the washing liquid reaches 7.0, and then dried at 150°C for 8 hours to obtain molecular sieve dD2.

[0097] 1000 g of molecular sieve dD2, 200 g of alumina monohydrate, 950 g of 3.5% nitric acid aqueous solution, 45 g of sesbania powder and 80 g of a polymer mixture (including 52 g of starch and 28 g of hexadecyltrimethylammonium bromide) are mixed and extruded into a cylindrical shape, and then treated at 135°C for 10 hours; 520°C for 4 hours; treated at 70°C for 2 hours with 5% ammonium chloride solution, and exchanged 4 times continuously; treated at 490°C in a saturated water vapor atmosphere for 7 hours; treated at 70°C for 4 hours with 1.5% oxalic acid solution to obtain the catalyst dE2.

[0098] The XRD of molecular sieve dD2 has typical ZSM-5 molecular sieve diffraction peaks. The static water initial contact angle value of molecular sieve dD2 is 41.5°, and the static benzene adsorption capacity is 124mg / g. The b-axis thickness of the molecular sieve is 163nm, and the exposure of the crystal plane perpendicular to the b-axis direction is 62%. The SiO2 / Al2O3 molar ratio of molecular sieve dD2 is 66.

[0099] Through testing, the micropore volume of catalyst dE2 is 0.10 cm 3 ·g -1 The mesopore volume is 0.59 cm 3 ·g -1 , mechanical strength is 94N / cm, bulk density is 0.53g·cm -3 .

[0100] [Comparative Example 3]

[0101] Compared with Example 1, the only difference is that an equal molar amount of 1,3-diphenyltetraethyldisilazane is used to replace diethylenetriaminopropylmethyldimethoxysilane. The specific preparation process of ZSM-5 molecular sieve and ZSM-5 molecular sieve catalyst is as follows:

[0102] 416.6 g of tetraethyl silicate, 20 g of aluminum sulfate 18hydrate, 576 g of water and 122 g of tetrapropylammonium hydroxide were mixed evenly, and then stirred at 30°C for 10 hours under closed conditions to obtain a mixture dA3; then 102.5 g of 1,3-diphenyltetraethyldisilazane was added to the above mixture dA3 and mixed evenly, and stirred at 110°C for 2 hours under closed conditions to obtain a mixture dB3, wherein tetraethyl silicate is calculated as SiO2: aluminum sulfate 18hydrate is calculated as Al2O3: water: tetrapropylammonium hydroxide: 1,3-diphenyltetraethyldisilazane = 1:0.015:16:0.3:0.15 (molar ratio). 69.3 g of the mixture dB3, 120 g of silicon powder, 20 g of aluminum sulfate 18 hydrate, 468 g of water, 44.1 g of diamine and 41 g of 1,3-diphenyltetraethyldisilazane were mixed to obtain a mixture dC3, wherein silicon powder was calculated as SiO2: aluminum sulfate 18 hydrate was calculated as Al2O3: water: n-butylamine: 1,3-diphenyltetraethyldisilazane = 1: 0.015: 13: 0.25: 0.06 (molar ratio). dC3 was crystallized at 165°C for 36 hours in a sealed container, then centrifuged to obtain a solid, washed the solid with deionized water for multiple times until the pH of the washing liquid reached 7.0, and then dried the washed solid at 150°C for 8 hours to obtain a molecular sieve dD3.

[0103] 1000 g of molecular sieve dD3, 200 g of alumina monohydrate, 950 g of 3.5% nitric acid aqueous solution, 45 g of sesbania powder and 80 g of a polymer mixture (including 52 g of starch and 28 g of hexadecyltrimethylammonium bromide) are mixed and extruded into a cylindrical shape, and then treated at 135°C for 10 hours; 520°C for 4 hours; treated at 70°C for 2 hours with 5% ammonium chloride solution, and exchanged 4 times continuously; treated at 490°C in a saturated water vapor atmosphere for 7 hours; treated at 70°C for 4 hours with 1.5% oxalic acid solution to obtain the catalyst dE3.

[0104] The XRD of molecular sieve dD3 has typical ZSM-5 molecular sieve diffraction peaks. The static water initial contact angle value of molecular sieve dD3 is 43.6°, and the static benzene adsorption capacity is 128mg / g. The b-axis thickness of the molecular sieve is 152nm, and the exposure of the crystal plane perpendicular to the b-axis direction is 51%. The SiO2 / Al2O3 molar ratio of molecular sieve dD3 is 66.

[0105] Through testing, the micropore volume of catalyst dE3 is 0.10cm 3 ·g -1 , the mesopore volume is 0.58 cm 3 ·g -1 , mechanical strength is 96N / cm, bulk density is 0.54g·cm -3 .

[0106] [Comparative Example 4]

[0107] Compared with Example 1, the only difference is that an equal molar amount of diethylenetriaminopropylmethyldimethoxysilane is used to replace 1,3-diphenyltetraethyldisilazane. The specific preparation process of ZSM-5 molecular sieve and ZSM-5 molecular sieve catalyst is as follows:

[0108] 416.6 g of tetraethyl silicate, 20 g of aluminum sulfate 18hydrate, 576 g of water and 122 g of tetrapropylammonium hydroxide were mixed evenly, and then stirred at 30°C for 10 hours under closed conditions to obtain a mixture dA4; then 74.8 g of diethylenetriaminopropylmethyldimethoxysilane was added to the above mixture dA4 and mixed evenly, and stirred at 110°C for 2 hours under closed conditions to obtain a mixture dB4, wherein tetraethyl silicate is calculated as SiO2: aluminum sulfate 18hydrate is calculated as Al2O3: water: tetrapropylammonium hydroxide: diethylenetriaminopropylmethyldimethoxysilane = 1:0.015:16:0.3:0.15 (molar ratio). 69.3 g of mixture dB4, 120 g of silicon powder, 20 g of aluminum sulfate 18 hydrate, 468 g of water, 44.1 g of diethylenetriamine and 29.9 g of diethylenetriamine propylmethyl dimethoxysilane were mixed to obtain mixture dC4, wherein silicon powder was calculated as SiO2: aluminum sulfate 18 hydrate was calculated as Al2O3: water: n-butylamine: diethylenetriamine propylmethyl dimethoxysilane = 1: 0.015: 13: 0.25: 0.06 (molar ratio). dC4 was crystallized at 165° C. for 36 h in a sealed container, then centrifuged to obtain a solid, washed the solid with deionized water for multiple times until the pH of the washing solution reached 7.0, and then dried the washed solid at 150° C. for 8 hours to obtain molecular sieve dD4.

[0109] 1000 g of molecular sieve dD4, 200 g of alumina monohydrate, 950 g of 3.5% nitric acid aqueous solution, 45 g of sesbania powder and 80 g of a polymer mixture (including 52 g of starch and 28 g of hexadecyltrimethylammonium bromide) are mixed and extruded into a cylindrical shape, and then treated at 135°C for 10 hours; 520°C for 4 hours; treated at 70°C for 2 hours with 5% ammonium chloride solution, and exchanged 4 times continuously; treated at 490°C in a saturated water vapor atmosphere for 7 hours; treated at 70°C for 4 hours with 1.5% oxalic acid solution to obtain the catalyst dE4.

[0110] The XRD of molecular sieve dD4 has typical ZSM-5 molecular sieve diffraction peaks. The static water initial contact angle value of molecular sieve dD4 is 41.6°, and the static benzene adsorption capacity is 115mg / g. The b-axis thickness of the molecular sieve is 178nm, and the exposure of the crystal plane perpendicular to the b-axis direction is 60%. The SiO2 / Al2O3 molar ratio of molecular sieve dD4 is 66.

[0111] Through testing, the micropore volume of catalyst dE4 is 0.09 cm 3 ·g -1 , the mesopore volume is 0.56 cm 3 ·g -1 , mechanical strength is 93N / cm, bulk density is 0.53g·cm -3 .

[0112] [Comparative Example 5]

[0113] Compared with Example 1, the only difference is that the temperature of the first sealing treatment is the same as that of the second sealing treatment.

[0114] 416.6 g of tetraethyl silicate, 20 g of aluminum sulfate 18hydrate, 576 g of water and 122 g of tetrapropylammonium hydroxide were mixed evenly, and then stirred at 110°C for 10 hours under closed conditions to obtain a mixture dA5; then 74.8 g of diethylenetriaminopropylmethyldimethoxysilane was added to the above mixture dA5 and mixed evenly, and stirred at 110°C for 2 hours under closed conditions to obtain a mixture dB5, wherein tetraethyl silicate is calculated as SiO2: aluminum sulfate 18hydrate is calculated as Al2O3: water: tetrapropylammonium hydroxide: diethylenetriaminopropylmethyldimethoxysilane = 1:0.015:16:0.3:0.15 (molar ratio). 69.3 g of mixture dB5, 120 g of silicon powder, 20 g of aluminum sulfate 18 hydrate, 468 g of water, 44.1 g of diamine and 41 g of 1,3-diphenyltetraethyldisilazane were mixed to obtain mixture dC5, wherein silicon powder was calculated as SiO2: aluminum sulfate 18 hydrate was calculated as Al2O3: water: n-butylamine: 1,3-diphenyltetraethyldisilazane = 1: 0.015: 13: 0.25: 0.06 (molar ratio). dC5 was crystallized at 165°C for 36 hours in a sealed container, then centrifuged to obtain a solid, washed the solid with deionized water for multiple times until the pH of the washing solution reached 7.0, and then dried the washed solid at 150°C for 8 hours to obtain molecular sieve dD5.

[0115] 1000 g of molecular sieve dD5, 200 g of alumina monohydrate, 950 g of 3.5% nitric acid aqueous solution, 45 g of sesbania powder and 80 g of a polymer mixture (including 52 g of starch and 28 g of hexadecyltrimethylammonium bromide) are mixed and extruded into a cylindrical shape, and then treated at 135°C for 10 hours; 520°C for 4 hours; treated at 70°C for 2 hours with 5% ammonium chloride solution, and exchanged 4 times continuously; treated at 490°C in a saturated water vapor atmosphere for 7 hours; treated at 70°C for 4 hours with 1.5% oxalic acid solution to obtain the catalyst dE5.

[0116] The XRD of molecular sieve dD5 has typical ZSM-5 molecular sieve diffraction peaks. The static water initial contact angle value of molecular sieve dD5 is 92.3°, and the static benzene adsorption capacity is 165mg / g. The b-axis thickness of the molecular sieve is 220nm, and the exposure of the crystal plane perpendicular to the b-axis direction is 58%. The SiO2 / Al2O3 molar ratio of molecular sieve dD5 is 66.

[0117] Through testing, the micropore volume of catalyst dE5 is 0.09 cm 3 ·g -1 , the mesopore volume is 0.52cm 3 ·g -1 , mechanical strength is 97N / cm, bulk density is 0.54g·cm -3 .

[0118] [Examples 4-6]

[0119] Catalysts E1-E3 prepared in Examples 1-3 were respectively applied to the alkylation of benzene to produce ethylbenzene, wherein the ethylene mass concentration was 70%, the reaction temperature was 320°C, the pressure was 2.2 MPa, and the ethylene mass space velocity was 3 h -1 The test was conducted under the condition that the molar ratio of benzene to ethylene was 5.2. The ethylene conversion rate and the ethyl selectivity in the alkylation product were tested. The test results are shown in Table 1.

[0120] Catalysts E1-E3 prepared in Examples 1-3 were tested for their one-way life in the reaction of benzene alkylation to ethylbenzene under ultra-high ethylene mass space velocity reaction conditions, wherein the ethylene mass concentration was 70%, the reaction temperature was 320°C, the pressure was 2.2 MPa, and the ethylene mass space velocity was 8 h -1 The test was conducted under the condition that the molar ratio of benzene to ethylene was 5.2. The single-pass life refers to the time from the start of the reaction to the time when the ethylene conversion rate drops to 50% of the initial conversion rate. The test results are shown in Table 1.

[0121] [Comparative Examples 6-10]

[0122] Catalysts dE1-dE5 prepared in Comparative Examples 1-5 were respectively applied to the alkylation of benzene to produce ethylbenzene, wherein the ethylene mass concentration was 70%, the reaction temperature was 320°C, the pressure was 2.2 MPa, and the ethylene mass space velocity was 3 h -1 The test was conducted under the condition that the molar ratio of benzene to ethylene was 5.2. The ethylene conversion rate and the ethyl selectivity in the alkylation product were tested. The test results are shown in Table 1.

[0123] The catalysts dE1-dE5 prepared in Comparative Examples 1-5 were tested for their single-pass life in the reaction of benzene alkylation to ethylbenzene under ultra-high ethylene mass space velocity reaction conditions, wherein the ethylene mass concentration was 70%, the reaction temperature was 320°C, the pressure was 2.2 MPa, and the ethylene mass space velocity was 8 h -1 The test was conducted under the condition that the molar ratio of benzene to ethylene was 5.2. The single-pass life refers to the time from the start of the reaction to the time when the ethylene conversion rate drops to 50% of the initial conversion rate. The test results are shown in Table 1.

[0124] Table 1 Test results of the catalysts obtained in each example

[0125] Catalyst No. Ethylene conversion, wt% Ethyl selectivity, wt% One-way life, h E1 99.5 99.7 412 E2 99.6 99.8 423 E3 99.3 99.7 405 dE1 98.6 99.2 315 dE2 98.0 99.0 286 dE3 98.3 98.4 302 dE4 97.8 99.0 278 dE5 97.2 98.9 243

[0126] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a ZSM-5 molecular sieve, comprising: (a) mixing a silicon source I, an aluminum source I, water and a template agent I, and subjecting the mixture to a first sealing treatment to obtain a mixture A; (b) mixing the mixture A and the organic matter I, and subjecting the mixture to a second sealing treatment to obtain a mixture B; (c) mixing mixture B, silicon source II, aluminum source II, water, template II and organic matter II to obtain mixture C; (d) crystallizing the mixture C, performing liquid-solid separation, washing, and drying to obtain the molecular sieve; The first sealed treatment conditions are: temperature 10-40°C, time 5-15 hours; the second sealed treatment conditions are: temperature 80-130°C, time 1-5 hours.

2. The preparation method according to claim 1, characterized in that: In step (a), the silicon source I is one or more of tetraethyl silicate, tetrapropyl silicate, and tetrabutyl silicate; and / or, the aluminum source I in step (a) is one or more of aluminum sulfate, aluminum isopropoxide, sodium aluminate, and pseudo-boehmite; and / or, the template I in step (a) is one or more of tetrapropylammonium hydroxide, ethylamine, ethylenediamine, n-butylamine, butanediamine, hexamethyleneimine, piperidine, piperazine, and homopiperazine; Preferably, in step (a), the molar ratios of silicon source I, aluminum source I, water and template I are respectively silicon source I: aluminum source I: water: template I = 1: (0.0025-0.025): (5-20): (0.1-1.0), wherein silicon source I and aluminum source I are calculated as SiO2 and Al2O3, respectively.

3. The preparation method according to claim 1, characterized in that: In step (b), the organic substance I is an aminopropyl-containing silane, preferably one or more of diethylenetriaminopropylmethyldimethoxysilane, N-aminoethyl-3-aminopropylmethyldiethoxysilane or N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane; Preferably, the molar ratio of the organic matter I to the mixture A calculated as SiO2 is organic matter I:SiO2=(0.02-0.3):

1.

4. The preparation method according to claim 1, characterized in that: In step (c), the silicon source II is one or more of silica sol, white carbon black, silicon powder, tetramethyl silicate, tetraethyl silicate, tetrapropyl silicate, and tetrabutyl silicate; and / or, in step (c), the aluminum source II is one or more of aluminum nitrate, aluminum chloride, aluminum sulfate, aluminum isopropoxide, sodium aluminate, and pseudo-boehmite; and / or, in step (c), the template agent II is one or more of tetrapropylammonium bromide, tetrapropylammonium hydroxide, ethylamine, ethylenediamine, n-propylamine, propylenediamine, n-butylamine, butylenediamine, n-hexylamine, hexamethylenediamine, ammonia water, hexamethyleneimine, piperidine, piperazine, and homopiperazine; and / or, in step (c), the organic matter II is a disilazane containing phenyl, preferably one or more of 1,3-diphenyltetraethyldisilazane, 1,3-dichloro-1,1,3,3-tetraphenyldisilazane, or 1,3-dimethyl-1,1,3,3-tetraphenyldisilazane; Preferably, in step (c), the molar ratios of silicon source II, aluminum source II, water, template II and organic matter II are, respectively, silicon source II: aluminum source II: water: template II: organic matter II = 1: (0.0025-0.025): (8-20): (0.1-0.3): (0.005-0.20); and / or, the ratio of the mass of the mixture B to the total mass of the five substances, silicon source II, aluminum source II, water, template II and organic matter II is (0.04-0.22): 1, wherein the silicon source II and the aluminum source II are calculated as SiO2 and Al2O3, respectively.

5. The preparation method according to claim 1, characterized in that: The crystallization conditions in step (d) are crystallization at 130-180° C. for 12-60 hours under closed conditions.

6. ZSM-5 molecular sieve prepared by the preparation method according to any one of claims 1 to 5.

7. The molecular sieve according to claim 6, characterized in that: The static water initial contact angle of the molecular sieve is 110-160°, and the static benzene adsorption capacity is 180-230 mg / g.

8. The molecular sieve according to claim 6, characterized in that: The b-axis thickness of the molecular sieve is 10-95 nm, preferably 30-90 nm, and the exposure of the crystal plane perpendicular to the b-axis is 67%-78%, preferably 65%-76%.

9. The molecular sieve according to claim 6, characterized in that: The SiO2 / Al2O3 molar ratio of the molecular sieve is 40-400.

10. A catalyst for preparing ethylbenzene by alkylation of benzene, characterized in that: The catalyst comprises a ZSM-5 molecular sieve prepared by the preparation method according to any one of claims 1 to 5, and optionally comprises alumina.

11. The catalyst according to claim 10, characterized in that: The catalyst has a molecular sieve content of more than 80%, preferably 80%-90%, and an alumina content of less than 20%, preferably 10%-20%, based on the mass of the catalyst.

12. The catalyst according to claim 10, characterized in that: The micropore volume of the catalyst is 0.12-0.16 cm 3 ·g -1 , the mesopore volume is 0.42-0.80cm 3 ·g -1 , mechanical strength is 70-110N / cm, bulk density is 0.51-0.65g·cm -3 .

13. A method for preparing a catalyst for preparing ethylbenzene by alkylation of benzene, comprising: (d) The ZSM-5 molecular sieve prepared by any of the methods described in claims 1 to 5, alumina and a polymer mixture are mixed and molded, and then dried, calcined, ammonium exchanged, steam treated, and acid washed to obtain the catalyst.

14. The preparation method according to claim 13, characterized in that: The alumina in step (e) is alumina monohydrate; and / or the polymer mixture in step (e) is a mixture of starch and at least one substance selected from cetyltrimethylammonium bromide, P123 or F127, wherein the mass ratio of starch to the polymer mixture is 60%-70%; Preferably, in step (e), the mass ratio of molecular sieve, alumina and polymer mixture is: molecular sieve: alumina: polymer mixture = 1: (0.1-0.3): (0.05-0.1); Preferably, in step (e), the drying condition is 120-150°C for 5-15 hours; the roasting condition is 400-600°C for 4-10 hours; the steam treatment condition is 420-520°C in a saturated steam atmosphere for 4-10 hours; the pickling condition is 0.5%-3.0% by mass concentration of an acid solution at 20-90°C for 2-5 hours.

15. A method for preparing ethylbenzene by alkylation of benzene, characterized in that: The reaction raw materials benzene and ethylene are contacted with the catalyst described in any one of claims 10-12 or the catalyst prepared by the method described in any one of claims 13-14 to generate ethylbenzene.

16. The method according to claim 15, characterized in that: The ethylene mass concentration in the ethylene feedstock is 8%-100%; and / or, the reaction conditions are as follows: the reaction temperature is 300-380°C, the reaction pressure is 0.4-2.5MPa, and the ethylene mass space velocity is 0.1-3.0h -1 , the molar ratio of benzene to ethylene is 4.0-6.0.

Citation Information

Patent Citations

  • Method for preparing ethylbenzene by alkylation of dry gas and benzene

    CN102875316A

  • Preparation method of high-selectivity benzene alkylation strip-shaped catalyst

    CN108080019A

  • High-performance mesoporous-micro double hole controllable molecular sieve adsorbent and preparation and application thereof

    CN105251441A

  • Sheet-shaped heteroatom molecular sieve and green synthesizing method thereof

    CN109607560A

  • HZSM-5 molecular sieve catalyst as well as preparation method and application thereof

    CN109876851A